Regulated expression of foreign genes in mammalian cells under the control of coliphage T3 RNA polymerase and lac repressor. - Deuschle, U (1989)
Systems that stringently regulate the expression of individual genes within a complex genetic background have contributed greatly to the analysis of gene function. In this report the development of a highly regulated expression system in mammalian cells is described in which transcription of a foreign gene is mediated by the bacteriophage T3 RNA polymerase under the control of the Escherichia coli lac repressor. Rabbit kidney cell lines have been established that constitutively express the phage RNA polymerase and lac repressor. The two bacterial proteins regulate the transcription of the coding sequence of the firefly luciferase, which has been placed under the control of a T3 promoter/lac operator fusion. In the presence of the inducer isopropyl beta-D-thiogalactoside, efficient T3 polymerase-dependent transcription is observed, which is tightly repressed in the absence of inducer. Translation of the T3 transcripts can be mediated by vaccinia virus functions. The demonstration that a specific transcription activity can be regulated over a range of several orders of magnitude in higher eukaryotic cells by using a highly specific and nontoxic inducer has broad implications for a variety of studies.